STUDI PERILAKU PADA SAMBUNGAN RECTANGULAR CONCRETE FILLED TUBES (RCFT) DENGAN METODE FINITE ELEMENT - Cintantya Budi Casita; Budi Suswanto (Journal of Civil Engineering, 2017)
This research presents the result of two rectangular filled tube column-to-beam connections under cyclic loadingusing finite element analysis. Connections of all two models were using weld connection and shear tab attached to beamwebs. In this study, 2 models were made: RR-1 and RB-2, which are RCFT connection with RBS and RCFT connectionwithout RBS. This study is conducted to learn, the advantages of RCFT connection with RBS against RCFT connectionwithout RBS. The analysis results observed that cyclic performance of the RBS moment connection was much superior to theconnection without RBS. The highest regions of stress occur in vicinity of beam bottom flange near column face forconnection without RBS. For connection with RBS, the highest regions of stress occur in reduced beam section of the beam.